Time and Space Use of Adults with Intellectual Disabilities - Terry K. Crowe; Jessica Salazar Sedillo; Emily F. Kertcher; Joy H. LaSalle MA (Scholarworks @ WMU, 2015)
Purpose: This study analyzed the time and space use of adults with intellectual disabilities (ID) in order to better understand the occupational patterns of this population. Methods: Time and space use data were collected through observation of 15 adults with ID during 4-hour periods on typical weekdays and weekend days. Data were coded into 12 time and 10 space use descriptive categories. Results: The participants used a greater variety of locations during weekdays that contributed to greater amounts of weekday time spent in a wider variety of activity categories. In contrast, the participants spent a majority of the observed weekend day time in the group home with less activity variety. Although the participants in this study lived in group homes and participated in day habilitation programs or supported employment, a majority of their midday time use occurred in passive activity categories in a minimum variety of locations. These results may be due to the types of activities offered by structured day habilitation programs and group homes. Conclusion: Occupational therapists may be key players to enhance the environments of people with ID by providing direct service and staff training to facilitate more diversity of active use of time and space for adults with ID.